2‐Hydroxy‐phytanoyl‐CoA lyase (AtHPCL) is involved in phytol metabolism in Arabidopsis. (22nd December 2021) - Yang, Wentao; Gutbrod, Philipp; Gutbrod, Katharina; Peisker, Helga; Song, Xiaoning; Falz, Anna‐Lena; Meyer, Andreas J.; Dörmann, Peter
SUMMARY: During chlorophyll degradation, large amounts of the isoprenoid alcohol phytol are released. The pathway of phytol catabolism has been studied in humans, because chlorophyll is part of the human diet, but little is known for plants. In humans, phytanoyl‐CoA derived from phytol is degraded via α‐oxidation by phytanoyl‐CoA hydroxylase (PAHX) and 2‐hydroxy‐phytanoyl‐CoA lyase (HPCL). Arabidopsis contains two sequences homologous to the human proteins AtPAHX and AtHPCL. Insertional mutants of Arabidopsis ( pahx, hpcl ) were grown under N deprivation to stimulate chlorophyll breakdown or supplemented with phytol to increase the endogenous amount of phytol. During N deprivation, chlorophyll, phytol, phytenal, upstream metabolites of phytol breakdown, and tocopherol and fatty acid phytyl esters, alternative phytol‐derived lipids, accumulated in pahx and hpcl mutants, in line with the scenario that the mutations interfere with phytol degradation. AtHPCL was localized to the peroxisomes. Expression analysis of the AtHPCL sequence in the yeast Δ pxp1 or Δ mpo1 mutants followed by supplementation with 2‐hydroxy‐palmitic acid and enzyme assays of peroxisomal proteins from Col‐0 and hpcl plants with 2‐hydroxy‐stearoyl‐CoA revealed that AtHPCL harbors 2‐hydroxy‐acyl‐CoA lyase activity. The α‐dioxygenases αDOX1 and αDOX2 are involved in α‐oxidation of fatty acids and could be involved in an alternative pathway of phytol degradation. However, phytol‐related lipids in the αdox1, αdox2, or αdox1 αdox2 mutants were not altered compared with Col‐0, indicating that αDOX1 and αDOX2 are not involved in phytol degradation. These results demonstrate that phytol degradation in Arabidopsis involves α‐oxidation by AtPAHX and AtHPCL, but that it is independent of αDOX1/αDOX2. Significance Statement: The degradation and turnover of phytol, the hydrophobic anchor of chlorophyll, in plants is poorly understood. We show here that phytol degradation in Arabidopsis proceeds via α‐oxidation catalyzed by phytanoyl‐CoA hydroxylase (PAHX) and 2‐hydroxy‐phytanoyl‐CoA lyase (HPCL), but is independent of the α‐dioxygenases αDOX1 and αDOX2. Therefore, the pathway of phytol degradation is related to the respective human pathway.